DIGITALIZATION IN EDUCATION - Ria Anggraini; Yosi Handayani (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2021)
Business today cannot be separated from issues that relate to sustainable development. For example, business is often accused Technology has altered the way people are conducting their business by utilizing information systems (IS). The velocity of development of IS has been perceived as a knout in conducting business in many sectors such as educational institutions, profit, and non-profit companies, government, and other areas. However, the development of IS has encouraged people to catch up with the pace of technology by digitalizing their work to take advantage of and compete with people in the world. Moreover, information system skills have become essential for recruiters, as companies use technology for their activities. Therefore, education’s role becomes very vital to create a better education system to produce well-equipped people for companies. This paper presents such a review for highlighting the progress and aims to help improve the awareness on the best experiences of creating an active teaching and learning method by integrating the information technology knowledge. It is intended to provide a clear idea for those wishing to generate a road map for digitizing the most technology used in education. Note that, this literature review provides a concrete explanation about curriculum, eLearning, artificial intelligence (AI), and gamification which are implemented and used in education, and categorizes the discussion based on the methodology of literature, Technology Used, and Year. This literature review will provide information on research from 2009 to 2019 that has been conducted regarding digitalization in education and review gaps in the literature for future research.